The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/smll.201803239
|View full text |Cite
|
Sign up to set email alerts
|

Intracameral Delivery of Layer‐by‐Layer Coated siRNA Nanoparticles for Glaucoma Therapy

Abstract: Glaucoma is the second leading cause of blindness worldwide, often associated with elevated intraocular pressure. Connective tissue growth factor (CTGF) is a mediator of pathological effects in the trabecular meshwork (TM) and Schlemm’s canal (SC). A novel, causative therapeutic concept which involves the intracameral delivery of small interfering RNA against CTGF is proposed. Layer-by-layer coated nanoparticles of 200–260 nm with a final layer of hyaluronan (HA) are developed. The HA-coating should provide th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…10 Should repeated administration be required to reduce IOP appropriately, a minimally invasive approach has been reported for periodic retrograde introduction of low-molecular-weight compounds into SC via the episcleral veins, and this could be used for non-invasive delivery of siRNA without adaptation (Retroject, Chapel Hill, NC, USA). Moreover, Dillinger et al 19 have recently shown that coating nanoparticles with hyaluronan more efficiently targets siRNA to TM and SC endothelial cells in view of the fact that such particles bind to the cell surface antigen CD44, present in greater quantities on cells of the outflow tissues. In conclusion, this study demonstrates in a well-characterized model of steroid-induced OHT a proof of concept of an siRNA-based therapeutic approach for IOP reduction.…”
Section: Discussionmentioning
confidence: 99%
“…10 Should repeated administration be required to reduce IOP appropriately, a minimally invasive approach has been reported for periodic retrograde introduction of low-molecular-weight compounds into SC via the episcleral veins, and this could be used for non-invasive delivery of siRNA without adaptation (Retroject, Chapel Hill, NC, USA). Moreover, Dillinger et al 19 have recently shown that coating nanoparticles with hyaluronan more efficiently targets siRNA to TM and SC endothelial cells in view of the fact that such particles bind to the cell surface antigen CD44, present in greater quantities on cells of the outflow tissues. In conclusion, this study demonstrates in a well-characterized model of steroid-induced OHT a proof of concept of an siRNA-based therapeutic approach for IOP reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting CTGF-induced extracellular matrix production does not interfere with TGF β -2 pleiotropic effects, therefore targeting CTGF may prove beneficial and safer in the treatment of glaucoma. Recently, the intracameral delivery of anti-CTGF small interfering RNA (siRNA) by using nanoparticles coated by hyaluronan succeeded to penetrate deeply in the outflow region and showed binding of hyaluronan to the CD44 receptors, which were overexpressed in glaucomatous eyes [ 60 ]. Hyaluronan-coated nanoparticles combined with RNA interference may provide a potential strategy for glaucoma therapy.…”
Section: New Targets For Iop-lowering and For Iop-independent Thermentioning
confidence: 99%
“…Dillinger et al [16] proposed a novel, causative therapeutic idea which involves delivering small interfering RNA against CTGF via the intracameral route. A final layer of hyaluronan (HA) with layer-by-layer coated nanoparticles of 200–260 nm were synthesized.…”
Section: Replacement and Regeneration Of The Trabecular Meshwork (Tm)mentioning
confidence: 99%
“…The injection of nanoparticles is done through the anterior chamber and is perceived to follow the normal trabecular drainage pathway. Reproduced from ref [15,16] with permission from WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation